India - Andhra Pradesh Drought Adaptation Initiative : Lessons from Community-based Adaptation Approaches to Strengthen Climate Resilience - World Bank (World Bank, 2012)
This report presents the impact and lessons learned from the Andhra Pradesh Drought Adaptation Initiative (APDAI). The APDAI was implemented as a package of pilot activities in two dryland districts in Andhra Pradesh (Anantapur and Mahbubnagar) with the aim of developing and testing approaches for natural resource-based economic activities to better respond to current climate variability and long-term consequences of climate change. The report discusses how innovations are being scaled up through integration into regular government programs for greater outreach.